Giant Fibroepithelial Polyp in the Renal Pelvis to the Upper Ureter - Kyung Jin Chung (Urogenital Tract Infection)
Benign ureteral tumors are rare owing to the predominance of malignancies in ureter tumors. Among them, fibroepithelial polyps are very rare, and giant fibroepithelial polyps are even rarer. This paper reports the author’s experience of giant fibroepithelial polyps detected incidentally. A 47-year-old woman was referred for severe right flank pain to the author’s center. A kidney computed tomogram revealed a long soft tissue lesion in the right kidney, upper polar calyx, pelvis, and whole proximal ureter with hydronephrosis. The radiologic reading was right renal pelvis urothelial cancer. Endoscopic removal was deemed impossible because the mass was filling the entire renal pelvis and upper ureter, so a nephroureterectomy was performed. After the nephroureterectomy, the pathology findings revealed a giant fibroepithelial polyp. This paper reports the treatment of giant fibroepithelial polyps of the ureter. Clinicians should consider the possibility of benign tumors and recommend a cautious approach to treatment if discovered.